The Criminal Policy On Regulation Concerning Black Magic In Indonesian Law - Hendrik Hendrik; Henny Damaryanti; Budimansyah Budimansyah (STKIP Singkawang, 2018)
The black magic is a crime in which the black magic practioner can be regarded as a bandit. In the perspective of religious teachings, to study, to teach, to channelize and to use the services of black magic is a forbidden thing so that it becomes the legal law in the society. Criminal policy of resolving black magic criminality required the panel law to be a mean since the effect of the black magic can make the victim sustain injury and more ironically death. This research entitled criminal policy of black magic management in the positive law of Indonesia. The problem of this research is how the criminal policy of black magic management in the positive law of Indonesia. This research is a normative juridical research, where the data which are used in this research is secondary data; namely books, legislation, documents and other writing related to the problem being researched. Based on the result of the research about criminal policy in managing the black magic is needed to resolve black magic criminality and wide effect which can be caused by the black magic itself both from victim side and the black magic practioner side and from the society’s persecuted action by accusing him as a black magic practioner. The criminality of black magic exists in the article of 239 of Criminal Code (KUHP), by way of punishing everybody who claims that he has supernatural power, disclosing, giving hope, and offering services to others.